2014
DOI: 10.1007/s10578-014-0467-1
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Proneness to Shame and Guilt Predict Risky and Illegal Behaviors in Young Adulthood

Abstract: Do shame and guilt help people avoid doing wrong? Although some research suggests that guilt-proneness is a protective factor while shame-proneness puts individuals at risk, most research is either cross-sectional or short-term. In this longitudinal study, 380 5th graders (ages 10–12) completed measures of proneness to shame and guilt. We re-interviewed 68% of participants after they turned 18 years old (range 18–21). Guilt-proneness assessed in childhood predicted fewer sexual partners, less use of illegal dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 56 publications
5
58
0
4
Order By: Relevance
“…Therefore, two meta-analyses will be conducted, assessing the relation between guilt and delinquency, and shame and delinquency. (Stuewig et al, 2015;Tangney, 1996), making it difficult to assess the unique influence of guilt and shame on delinquency. However, as we expect that guilt is stronger associated with delinquency than shame, "shame-free" guilt may show stronger associations A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Therefore, two meta-analyses will be conducted, assessing the relation between guilt and delinquency, and shame and delinquency. (Stuewig et al, 2015;Tangney, 1996), making it difficult to assess the unique influence of guilt and shame on delinquency. However, as we expect that guilt is stronger associated with delinquency than shame, "shame-free" guilt may show stronger associations A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…One study found a link between daily shame and hostility in a community sample of adolescents with BPD features, but no association between daily guilt and hostility (Scott et al, 2015). Several studies have demonstrated guilt as protective compared to shame as a risk factor for a number of BPD-related impulsive symptoms, such as deliberate self-harm (VanDerhei, Rojahn, Stuewig, & McKnight, 2013), substance abuse (Dearing, Stuewig, & Tangney, 2005; Jeffrey Stuewig et al, 2015), and risky sexual behavior (Jeffrey Stuewig et al, 2015); however, no study has examined the differential contributions of shame and guilt to how BPD features may relate to the various forms of externalizing blame and anger expression. It seems plausible that while the intense shame characteristic of BPD may contribute to these problems as efforts to avoid the distress of shame (Schoenleber & Berenbaum, 2012), this tendency to focus on the global self as negative may occur in concert with less specific, action-focused thought and thus less adaptive guilt.…”
mentioning
confidence: 99%
“…In the fourth and final paper, Stuewig et al [12] present a study that examined whether children's proneness to guilt and shame predict risky and illegal behaviors in young adulthood. A sample of 380 children completed a measure of guilt and shame proneness when they were 10-12 years old, while teachers provided ratings of children's level of aggression at that time.…”
mentioning
confidence: 99%